A Brief View of the International Federation of Library Associations and Institutions World Library & Information Congress (IFLA WLIC 2017) in Wroclaw, Poland. Issue 4 (2nd October 2017) - Kear, Robin
ABSTRACT: A review of select sessions at the IFLA WLIC Congress in August 2017.